Evaluation of physical changes due to simulated loading on prosthetic screw supporting 4- and 6-unit implant prosthesis: An in vitro study - Mansi Singh; Akshay Bhargava; Abhishek Nagpal; Aditya Chaudhary (Wolters Kluwer Medknow Publications, 2022)
Aim: Screw loosening is a very common cause of failures in implant prosthodontics. In order to avoid screw fracture, it is imperative to understand the mechanical behavior of the screw and the dynamics it is subjected to intraorally. The present study was conducted to qualitatively evaluate and compare the morphological changes, surface defects, and cracks observed under a scanning electron microscope (SEM) in the prosthetic screw. Settings and Design: Two Stainless steel edentulous mandible models were fabricated on the basis of all on four and all on six concepts by using CAD design. Screw retained prosthesis were fabricated for both the models and total number of 80 prosthetic screws were made up of Ti6Al4V. Materials and Methods: Eighty prosthetic screws (N = 80) used in four- and six-unit implant-retained cast hybrid denture were subjected to cyclic loading of 1.5 million cycles and 3 million cycles, simulating a 5 and 10 years of usage, respectively. Once the simulated cycles had been completed in all subgroups, each prosthetic screw was inspected under SEM (×150-×1000) for any changes. Statistical Analysis: The data thus obtained were statistically analyzed using SPSS 12.0 software and P < 0.005 was considered statistically significant. Results: The study revealed statistically significant (P < 0.005) changes (like morphological changes, surface defects, crack initiation, and propagation) in the prosthetic screws after exposing them to predefined test conditions (P < 0.001). Conclusion: It can be concluded that the prosthetic screws need to be changed after a period of clinical use of 5 years irrespective of the number of implants used for rehabilitation. Further, the tilt of the abutment and numbers of implants also contribute to the stresses on the implant-supported prostheses.